BIOEKOLOGI TUMBUHAN NYAMPLUNG (Calophyllum inophyllum) DI PANTAI KURANJI, KABUPATEN LOMBOK BARAT - Nuraini; Hendriawan; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2025)
This study aims to analyze the bioecology of the Tamanu plant (Calophyllum inophyllum) on Kuranji Beach, West Lombok Regency. The method used was direct observation by measuring soil temperature, soil pH, and soil moisture in the plant's habitat. The results showed that the soil temperature was 35°C, soil pH 6.7, and soil moisture 1.8, indicating dry conditions. These conditions reflect the characteristics of coastal environments with high temperatures and low water availability. Soil temperature plays a role in plant metabolic activity, soil pH affects nutrient availability, while soil moisture is the main limiting factor in growth. Nevertheless, nyamplung is able to adapt well to these conditions so it can still grow in coastal environments.